Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Playing Pokémon Go on Wellness

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Theoretically, the gameplay would strengthen existing friendships and encourage to make new friends. However, the correlation between playing Pokémon and social well-being was not statistically significant [14]. Nevertheless, the social nature of AR games facilitates the formation of player networks, both locally and internationally.…”
Section: Social Health and Ar Gamementioning
confidence: 84%
See 1 more Smart Citation
“…Theoretically, the gameplay would strengthen existing friendships and encourage to make new friends. However, the correlation between playing Pokémon and social well-being was not statistically significant [14]. Nevertheless, the social nature of AR games facilitates the formation of player networks, both locally and internationally.…”
Section: Social Health and Ar Gamementioning
confidence: 84%
“…Further, playing the game could bring positive impacts on players' emotional wellness which predicted enhanced overall well-being [14]. However, the reasons why playing AR game associated with players' mental health has not yet been fully explored.…”
Section: Mental Health and Ar Gamementioning
confidence: 99%
“…Ewell and colleagues [ 27 ] also reported that daily time spent playing the game led to greater social interaction with both friends and strangers. However, Nikou and colleagues [ 64 ] reported contrasting findings that Pokémon GO play was not significantly associated with social integration, suggesting individuals perhaps play the game with existing friends rather than forming new relationships. Based on the findings, we speculate that although players do encounter strangers and new neighbors while playing the game, those encounters may not reach the significant magnitude, or the new relationships will not be sustained to make meaningful lasting interactions [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Nikou and colleagues [ 64 ] reported contrasting findings that Pokémon GO play was not significantly associated with social integration, suggesting individuals perhaps play the game with existing friends rather than forming new relationships. Based on the findings, we speculate that although players do encounter strangers and new neighbors while playing the game, those encounters may not reach the significant magnitude, or the new relationships will not be sustained to make meaningful lasting interactions [ 64 ]. Another plausible reason for the mixed findings may be due to various samples, as individuals had different motivations for playing the game and those who played the game with the goal of increasing PA or having fun did not perceive that they had much social interaction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation